A Influência da Referência de Tensão na Avaliação de Indicadores de Qualidade de Energia - Marafão, Fernando Pinhabel [UNESP]; Deckmann, Sigmar Maurer; Morales Paredes, Helmo Kelis (Institute of Electrical and Electronics Engineers (IEEE), 2008)
This paper discusses the importance of the voltage referential for power quality monitoring and power systempsilas instrumentation. Considering the operating conditions of simple power circuits, it will be demonstrated that an incorrect choice of the voltages referential may result in erroneous quantification of some power quality indices, especially in three-phase four wire circuits. The use of a virtual reference point and the neutral conductor as reference have been considered and the simulation results confirm the influence of the voltage reference selection in the evaluation of total harmonic distortion, unbalance factors and voltage sags. Finally a way of linking both methods will be discussed by means of Blakesleypsilas theorem. © Copyright 2010 IEEE - All Rights Reserved.
The influence of voltage referential in power quality indices evaluation
Keywords: Four-wire; Neutral conductor; Operating condition; Power circuit; Power quality indices; Power quality monitoring; Simulation result; Total harmonic distortions; Unbalance factor; Virtual reference point; Voltage reference; Voltage sags; Electric wiring; Quality control